2022
DOI: 10.3390/cells11152434
|View full text |Cite
|
Sign up to set email alerts
|

Add-On Cyclic Angiotensin-(1-7) with Cyclophosphamide Arrests Progressive Kidney Disease in Rats with ANCA Associated Glomerulonephritis

Abstract: Rapidly progressive crescentic glomerulonephritis associated with anti-neutrophil cytoplasmic antibodies (ANCA-GN) is a major cause of renal failure. Current immunosuppressive therapies are associated with severe side effects, intensifying the need for new therapeutic strategies. The activation of Mas receptor/Angiotensin-(1-7) axis exerted renoprotection in chronic kidney disease. Here, we investigated the effect of adding the lanthionine-stabilized cyclic form of angiotensin-1-7 [cAng-(1-7)] to cyclophospham… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…RPGN is clinically manifestations as a rapidly progressive renal failure and pathologically as crescentic and necrotizing lesions with infiltration of inflammatory cells in the glomeruli 14 . The autoimmune development of antibodies towards type IV collagen in the glomerular and alveolar basement membranes leads to patients typically presenting with RPGN and pulmonary hemorrhage 15–17 . Evidence of anti‐GBM antibodies in serum or histologically is required for diagnosis 18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RPGN is clinically manifestations as a rapidly progressive renal failure and pathologically as crescentic and necrotizing lesions with infiltration of inflammatory cells in the glomeruli 14 . The autoimmune development of antibodies towards type IV collagen in the glomerular and alveolar basement membranes leads to patients typically presenting with RPGN and pulmonary hemorrhage 15–17 . Evidence of anti‐GBM antibodies in serum or histologically is required for diagnosis 18 .…”
Section: Discussionmentioning
confidence: 99%
“…14 The autoimmune development of antibodies towards type IV collagen in the glomerular and alveolar basement membranes leads to patients typically presenting with RPGN and pulmonary hemorrhage. 15 , 16 , 17 Evidence of anti‐GBM antibodies in serum or histologically is required for diagnosis. 18 Treatment mainly involves the use of apheresis and intensive, strong immunosuppression such as cyclophosphamide.…”
Section: Discussionmentioning
confidence: 99%
“…Another paper published at the same time also showed that the coadministration of a low dose of nephrotoxic anti‐rat GBM serum enables this model to resemble the characteristic features of disease in humans 27 . Recently, the enhanced EAV rat model induced by human MPO and anti‐rat GBM serum has been put into use in a pre‐clinical therapeutic approach assessment 28 …”
Section: Classic Animal Models Of Mpo‐aavmentioning
confidence: 99%
“… 27 Recently, the enhanced EAV rat model induced by human MPO and anti‐rat GBM serum has been put into use in a pre‐clinical therapeutic approach assessment. 28 …”
Section: Classic Animal Models Of Mpo‐aavmentioning
confidence: 99%